2020
DOI: 10.1002/ccd.29320
|View full text |Cite
|
Sign up to set email alerts
|

Same day discharge after chronic total occlusion interventions: A single center experience

Abstract: Objectives To assess the feasibility and safety of same day discharge (SDD) after chronic total occlusion (CTO) percutaneous coronary intervention (PCI). Background CTO PCI has been associated with higher complication rates and procedural and hospitalization costs. Shortening post‐PCI hospitalization length not only increases the patients' comfort but at the same time it consists an important part of cost reduction policies. Methods We retrospectively compared the 30‐day outcomes of patients who underwent CTO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 32 publications
4
10
0
Order By: Relevance
“…[22][23][24][25] In a recent analysis of 173 patients who underwent CTO PCI between 2016 and 2019 in Greece, the SDD rate was 29.5%. 26 Similar to our study, SDD patients had fewer comorbidities. All SDD patients had forearm-only access (radial, ulnar, or snuffbox), and the 30-day incidence of MACE was comparable between the SDD and the non-SDD group (0.0% vs. 1.6%, p = 1.0).…”
Section: Discussionsupporting
confidence: 84%
“…[22][23][24][25] In a recent analysis of 173 patients who underwent CTO PCI between 2016 and 2019 in Greece, the SDD rate was 29.5%. 26 Similar to our study, SDD patients had fewer comorbidities. All SDD patients had forearm-only access (radial, ulnar, or snuffbox), and the 30-day incidence of MACE was comparable between the SDD and the non-SDD group (0.0% vs. 1.6%, p = 1.0).…”
Section: Discussionsupporting
confidence: 84%
“…Barker et al reported that of 467 patients undergoing percutaneous PFO closure, 456 had successful day-case surgeries, with low complication rates upon follow-up that were comparable to previous studies examining PFO closure complications [25]. While these studies have data showing that SDD is effective and feasible, this study is the first to examine the safety of SDD through analysis of 30-day MACE rates, a standard primary clinical endpoint for evaluating the safety of SDD after procedures involving catheterisation [10,[26][27][28][29]. All patients were followed-up with no 30-day MACE outcomes.…”
Section: Discussionsupporting
confidence: 55%
“…Even with the in creased anatomical and clinical complexity of PCIs in current practice (chronic coronary occlusion, left main coronary artery obstruction, multivessel disease), hospital discharge on the same day remains a feasible and safe strategy in most scenarios. 10,11 In our series, we noticed an increase in complexity of cases, demonstrated by an higher percentage of diabetic patients (28% versus 42%), greater number of bifurcation lesions (5% versus 15%), greater use of drug-eluting stents, and an increase in type B2 and C lesions (28% versus 46%), as shown in figure 2. These changes were not associated with an increase in adverse events.…”
Section: Discussionmentioning
confidence: 57%